Comparing Two Folate Receptor β-Targeted Tracers in a Rat Model of Experimental Autoimmune Myocarditis - Atencio Herre, Erika; Li, Xiang-Guo; Liljenbäck, Heidi; Palani, Senthil; Andriana, Putri; Jahandideh, Arghavan; Virta, Jenni; Iqbal, Imran; Dillemuth, Pyry; Kunnas, Jonne; Miner, Maxwell W.G.; Rajander, Johan; et al. (American Chemical Society (ACS), 2026)
Folate receptor β (FR-β) expression may serve as a marker of activated macrophages involved in autoimmune myocarditis. The positron emission tomography (PET) tracer N-succinimidyl 4-[18F]fluorobenzoate-conjugated folate ([18F]SFB-FOL) effectively targets FR-β-positive macrophages in rheumatoid arthritis. Here, we examined [18F]SFB-FOL for detecting myocardial inflammation via FR-β in a rat model of experimental autoimmune myocarditis (EAM), in comparison with the established FR-β-targeted PET tracer aluminum fluoride-18-labeled 1,4,7-triazacyclononane-1,4,7-triacetic acid-conjugated folate ([18F]FOL). EAM was induced in 22 Lewis rats through cardiac myosin immunization. Rats underwent 2-deoxy-2-[18F]fluoro-d-glucose ([18F]FDG) PET to visualize myocardium, followed by dynamic PET with [18F]SFB-FOL or [18F]FOL at Days 14, 21, or 28 postimmunization. Postimaging, myocardial tissues were assessed by γ-counting, autoradiography, and CD68 immunohistochemistry to quantify macrophage presence. Both tracers showed high radiochemical purity and in vivo stability. Inflammation-rich myocardial lesions were confirmed, with macrophages occupying 9.9% ± 1.1 of the tissue area. PET imaging revealed significantly higher uptake of both tracers in inflamed myocardium versus remote areas, confirmed by histology and autoradiography. Lesion-to-remote uptake ratios were 5.7 ± 1.8 for [18F]SFB-FOL and 3.8 ± 0.5 for [18F]FOL. Blood clearance and renal excretion were rapid for both tracers. No significant differences were observed in tracer uptake or macrophage density between Days 21 and 28. [18F]SFB-FOL is a suitable tracer for detecting active myocardial inflammation via FR-β in EAM and performs comparably to [18F]FOL.